Hyperbaric oxygen therapy positively interferes with oxidative metabolism in female cats undergoing video-assisted elective ovariohysterectomy - Martins, Letícia Reginato; FISCHBORN, Nadine Trinks; Mariga, Carollina; Griesang, Júlia Mariani; Andrade, Júlia Carneiro Rodrigues; Zarpellon, Alexandre Jacques; Dalmonin, Fabíola; Muller, Daniel Curvello de Mendonça; Soares, André Vasconcelos; Brun, Mauricio Veloso (Archives of Veterinary Science, 2023)
Knowing the low number of studies about the species chosen for the study in hyperbaric medicine and the importance that this technique has to help in several diseases and future studies. This study aimed to determine whether hyperbaric oxygen therapy (HBOT) alters oxidative biomarkers after elective ovariohysterectomy (OHE). For this purpose, 45 healthy female cats were randomized into three groups: the hyperbaric group (HG): 15 animals pretreated with HBOT and submitted to OHE; the hyperbaric control group (HCG): 15 animals pretreated with HBOT without surgery; and the sham group (SHAM): 15 female cats submitted to OHE without pretreatment. The following biomarkers were evaluated: superoxide dismutase (SOD) and catalase (CAT), reactive oxygen species (ROS), thiobarbituric acid reactive substances (TBARS), acetylcholinesterase (AChE), and butyrylcholinesterase (BChE). The collection times were: T1 = before the surgery for the operated groups and after sedation in the HCG; T2 = 30 min after reversal of sedation (HCG) or at the time of extubation in the other groups; T3 = 24 hr after T2. There was a stat. sign. increase in TBARS in the T3 SHAM compared to the T3 HG (P = 0.043). Moreover, it was observed a stat sign that CAT activity decreased in T2 SHAM and T3 SHAM compared to T1 SHAM (p=0.012 and p<0.001 mauric); T2 SHAM had lower CAT activity than T2 HCG (p=0.05). Additionally, the T3 SHAM was significantly lower than the T3 HG (p=0.030) and T3 HCG (p=0.050). It was observed a stat sign. reduction of SOD in the T2 SHAM compared to the T2 HG (p=0.033) and T2 HCG (p=0.027). Similarly, the T3 SHAM decreased compared to the T3 HG (p=0.039) and T3 HCG (p=0.019). The HBOT proved to be of value in promoting a favorable influence on reducing oxidative stress and serum levels of these biomarkers.